Laju Infiltrasi dan Permeabilitas Tanah pada Areal Kampus I Universitas Negeri Gorontalo - Pomalingo, Nelson; ., Nurdin (Jurnal Agroteknotropika, 2012)
Land utility for physic buildings on Gorontalo State University campus I has shown rasing significant trends. Whereas, the land was originally rice field productively and water catchments area. Consequently, its function is reduced due to the infiltration of water hampered. This study aimed to (a) determine the amount of soil infiltration rate, and (b) determine the amount of soil permeability. The study was conducted on six months in the campus 1 Gorontalo State University areas. The equipment consists of Guelph permeameter, rol meter, water bag, stop watch, soil bor and raffia. s, the materials consist of water and soil samples. Infiltration measurements carried out in a transect from the south to the north lines. Measurements will be performed at every five meters with two measurements (0-10 cm and 10-20 cm). On existing lines any building or standing crop, the measurement will be carried out on one side to detect the effect of distance and the soil variability. Parameters observed include water infiltration, and soil permeability. The result of this research shown that infiltration rate (i) and soil permeability (Ks) at campus 1 Gorontalo State University areas classified as very rapid. s, the highest of infiltration rate and soil permeability values was to 140 m distance or point 28 and the lowest was to 170 m distance or point 34.